CD14 is associated with biliary stricture formation. Issue 3 (20th April 2016) - Friedrich, Kilian; Smit, Mark; Brune, Maik; Giese, Thomas; Rupp, Christian; Wannhoff, Andreas; Kloeters, Petra; Leopold, Yvonne; Denk, Gerald Ulrich; Weiss, Karl Heinz; Stremmel, Wolfgang; Sauer, Peter; et al.
Abstract : The pathogenesis of intrahepatic biliary stricture formation in patients with primary sclerosing cholangitis (PSC) or after liver transplantation (LTx) remains elusive. CD14 receptor signaling is a key mediator of the innate immune system; its common genetic variant is associated with alcoholic liver disease. PSC and LTx cohort patients and primary biliary cirrhosis (PBC) control patients were genotyped for the CD14 ‐260C>T (rs2569190) polymorphism, and genotypes were correlated with long‐term clinical outcome. Biliary tissue, bile, and whole blood of PSC patients and healthy controls were screened for markers of the innate immune system and bacterial infection. In 121 PSC patients, the CD14 ‐260C>T genotype was associated with development of dominant bile duct strictures ( P = 0.02). In 365 LTx patients, TT carriers (4.1%) were protected against the formation of nonanastomotic biliary strictures versus CC/CT patients (12.6%; P = 0.01). Chemokine ligand 8 ( P = 0.04) and chemokine receptor 6 ( P = 0.004) were up‐regulated in biliary tissue of PSC patients with the TT versus the CC/CT genotype. Lipopolysaccharide whole‐blood stimulation resulted in a significant change in interleukin (IL)‐8 ( P = 0.05) and IL‐12p40 levels ( P = 0.04) in healthy control subjects carrying the TT genotype. TT PSC patients were protected against Gram‐negative bacterial biliary infection (TT: 0% vs. CC/CT: 22.5%; P = 0.02). Serum‐soluble CD14 levels correlated with the CD14 ‐260C>T genotype ( P = 0.02), representing an independent risk indicator of survival in PSC patients (hazard ratio, 0.40; 95% confidence interval, 0.19‐0.86; P =0.01). Conclusions : The function of the innate immune response by CD14 is crucial during biliary infection and stricture formation. The benefits of CD14 signaling modification should be addressed in future studies. (Hepatology 2016;64:843‐852)